The Relationship Between Teacher Pedagogic Competence and Principal's Leadership Competence on Student Interests and Learning Outcomes - Awalia, Hikmah; Rahmawati, Rahmawati; Alannasir, Wahyullah (ALENA : Journal of Elementary Education, 2025)
This study aims to determine how the relationship between teachers' pedagogical competence and principals' leadership competence, how the relationship between teachers' pedagogical competence and principals' leadership competence on grade v students' interest in learning and whether there is a positive and significant relationship between teachers' pedagogical competence and principals' leadership competence on the interest and learning outcomes of grade V students of SD Inpres Kalang Tubung II Makassar City. This type of research is ex post facto using quantitative research methods. The population of this study were all fifth grade students of SD Inpres Kalang Tubung II Makassar City, totaling 42 students. The samples of this study were randomly selected VA and VB classes totaling 29 people. The instruments used were questionnaires, tests and documentation. Data analysis techniques used are descriptive and inferential analysis. The results showed that: 1) An overview of the relationship between teacher pedagogical competence and principal leadership, both aspects play an important role in improving education in schools. 2) The description of the relationship between teacher pedagogical competence and principal leadership on student learning interest is interrelated. This can be seen from the pedagogical competence of teachers which includes the ability to design, implement and evaluate the learning process effectively plays a direct role in building an attractive environment for students so that it has an impact on student interest in learning and competent principals can ensure the availability of appropriate educational resources and strategies. 3) The picture of the relationship between teacher pedagogical competence and principal leadership competence has a positive and significant relationship to the interest and learning outcomes of fifth grade students of SD Inpres Kalang Tubung II Makassar City after hypothesis testing results were obtained with a significance value of 0.000 <0.05, meaning that there is a positive relationship between teacher pedagogical competence and principal leadership on student interest and learning outcomes.